Synthesis, crystal structure, DFT, Hirshfeld surface analysis, energy frameworks and in-Silico drug-targeting PFKFB3 kinase of novel triazolequinoxalin derivative (TZQ) as a therapeutic Strategy against cancer - Nadeem Abad; Fares Hezam Al-Ostoot; Sajda Ashraf; Karim Chkirate; Majed S. Aljohani; Hussam Y. Alharbi; Shafeek Buhlak; Mohamed El Hafi; Luc Van Meervelt; Basheer M. Al-Maswari; El Mokhtar Essassi; Youssef Ramli (Heliyon, 2023)
Overall, drug design is a dynamic and evolving field, with researchers constantly working to improve their understanding of molecular interactions, develop new computational methods, and explore innovative techniques for creating effective and safe medications. The process can involve steps such as the identification of targets, the discovery of lead compounds, lead optimization, preliminary testing, human trials, regulatory approval and finally post-marketing surveillance, all aimed at bringing a new drug from concept to market. In this article, the synthesis of the novel triazolequinoxalin (TZQ) 1-((1-hexyl-1H-1,2,3-triazol-5-yl)methyl)-3-phenylquinoxalin-2(1H)-one (4) is reported. The structure has been identified with a variety of spectroscopic methods (1H, 13C NMR, and LC-MS) and finally, the structure has been determined by X-ray diffraction (XRD) studies. The TZQ molecule has crystallized in the monoclinic space C2/c group with unit cell dimensions a = 41.201(2) Å, b = 10.6339(6) Å, c = 9.4997(4) Å, β = 93.904(4). The crystal structure is stabilized by intermolecular interactions (N–H ⋯ O and N–H … Cg) occurring within the molecule. The presence of these intermolecular interactions is evaluated through analysis of Hirshfeld surfaces (HS) and two-dimensional (2D) chemical fingerprints map. Additionally, energy frameworks were employed to identify the prevailing interaction energy influencing the molecular arrangement. Density Functional Theory (DFT) calculations were computed to establish concurrence between theoretical and experimental results. Furthermore, the HOMO-LUMO energy levels were determined using the B3LYP/6-31+G(d, p) level of theory. Finally, molecular docking was used to predict the anti-cancer activity of the compound (4) against PFKFB3 kinase and presented noticeable hydrophilic and hydrophobic interactions at the active site region.